THE STUDY EXAMINES THE STUDENTS' PERSPECTIVE ON SELF-EVALUATION IN THE ENGLISH LANGUAGE COURSE AT THE EIGHTH GRADE OF JUNIOR HIGH SCHOOL, AS-SALAFIYYAH PAMEKASAN - Eriyanto, Eriyanto (Jurnal Kajian Pendidikan dan Psikologi, 2024)
The research is to provide a comprehensive description of the students' viewpoint on self-evaluation in the English language course at the eighth grade of Junior High School, As-Salafiyyah Pamekasan. This research is of a qualitative nature. The data collection method involves administering questionnaires and conducting interviews with the students. The questionnaires are distributed to all students in both class C and class D. The data consists of information regarding students' perception of the importance of implementing self-assessment in the English language course. The methodology for analyzing the data includes three steps: 1) arranging the data, 2) organizing the data, and 3) drawing conclusions from the data. The study's findings indicate that nearly all of the students expressed the significance of implementing self-assessment in the English language subject. They believe that self-assessment enables them to identify their comprehension of the subject matter, recognize the challenges they encounter, and determine the necessary steps to enhance their understanding.